A lightweight technique for detection and prevention of wormhole attack in MANET - Ali Zardari, Zulfiqar; Ali Memon, Kamran; Shah, Reehan Ali; Dehraj, Sanaullah; Ahmed, Iftikhar (EAI Endorsed Transactions on Scalable Information Systems, 2020)
A mobile ad-hoc network (MANET) is an ordinary and self-orbiting communication network that is capable of managing mobile nodes. Many proposed protocols on MANET address its vulnerability against different threats and attacks. The malicious node exploits these vulnerabilities to lunch attacks, especially when nodes have mobility and network do not have constant topology, like wormhole attack. This paper presents a lightweight technique that detects the wormhole attacks in MANET. In the proposed technique, the source node calculates the average sequence number of the reply (RREP) packets. If the sequence number of the corresponding node exceeds the calculated average value of the sequence number, then all traffic is discarded, and the node is marked as malicious. The proposed technique is less complex, power-efficient, and enhances network lifetime as more data packets are delivered to the destination node. This technique is validated through comprehensive simulations results in NS2.